Dying in an avalanche: Current risks and their valuation - Andrea M. Leiter; Gerald J. Pruckner (University of Innsbruck, Department of Public Finance, 2008)
This paper examines the influence of implicit information on willingness to pay (WTP) values for prevention of the risk of dying in an avalanche. We present the results of a contingent valuation (CV) study carried out in Austria in two different periods (fall 2004 and winter 2005). The comparison of WTP results between the two waves allows identification of whether the immediate occurrence of avalanches and their attendant fatal accidents affect individual risk evaluations. Individuals state a lower WTP in winter despite the fact that avalanche accidents are predominant at that time. Personal responsibility for risk exposure and its associated voluntariness are the main reasons for the decrease in WTP from the fall to the winter period. Preferences for alternative protective measures (against car accidents and food poisoning) also lead to a decrease of WTP, while a higher risk perception and personal experience of avalanches reveal a positive influence. We conclude that the change in WTP across seasons is not arbitrary but can be explained by specific risk characteristics.
Keywords: D81; J17; Q51; Q54; 330; contingent valuation; willingness to pay; risk prevention; risk perception; Risikopräferenz; Naturkatastrophe; Willingness to pay; Australien